2019
DOI: 10.1177/2150135119885890
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Multistage Palliation of Infants With Single Ventricle and Atrioventricular Septal Defect

Abstract: Background: Published palliation outcomes of infants with functional single ventricle (SV) and common atrioventricular septal defect (AVSD) are poor due to associated cardiac and extracardiac anomalies and development of atrioventricular valve (AVV) regurgitation. We report current palliation results. Methods: From 2002 to 2012, 80 infants with functional SV with AVSD underwent multistage palliation. Competing-risks analyses modeled events after first-stage surgery and Glenn (death/transplantation vs next pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Patients with unbalanced AVSD are at greater risk for mortality compared with other single-ventricle anomalies; this is due to many factors, including genetic conditions (association with Down and heterotaxy syndromes), extracardiac malformations, and associated cardiac problems (atrioventricular valve regurgitation, heart block, pulmonary venous anomalies, double outlet right ventricle, etc). 9 At the same time, those studies, along with the current series from Devlin and colleagues, highlighted specific problems related to PAB in patients with unbalanced ASVD, especially those with dominant right ventricle and associated arch obstruction. [8][9][10][11] In those patients, initial palliation with PAB might produce double-outlet obstruction by intensifying the degree of left ventricular outflow tract obstruction (a well-recognized problem).…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 90%
See 3 more Smart Citations
“…Patients with unbalanced AVSD are at greater risk for mortality compared with other single-ventricle anomalies; this is due to many factors, including genetic conditions (association with Down and heterotaxy syndromes), extracardiac malformations, and associated cardiac problems (atrioventricular valve regurgitation, heart block, pulmonary venous anomalies, double outlet right ventricle, etc). 9 At the same time, those studies, along with the current series from Devlin and colleagues, highlighted specific problems related to PAB in patients with unbalanced ASVD, especially those with dominant right ventricle and associated arch obstruction. [8][9][10][11] In those patients, initial palliation with PAB might produce double-outlet obstruction by intensifying the degree of left ventricular outflow tract obstruction (a well-recognized problem).…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 90%
“…9 At the same time, those studies, along with the current series from Devlin and colleagues, highlighted specific problems related to PAB in patients with unbalanced ASVD, especially those with dominant right ventricle and associated arch obstruction. [8][9][10][11] In those patients, initial palliation with PAB might produce double-outlet obstruction by intensifying the degree of left ventricular outflow tract obstruction (a well-recognized problem). A different strategy such as aortopulmonary amalgamation and shunt might be a better approach in those patients.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 90%
See 2 more Smart Citations
“…16,17 Recently, we demonstrated that the outcomes of these patients were better than previously thought, with 60% of patients reaching Fontan completion and a 25-year survival of 80% in those patients who reached Fontan completion. 1,18 We have learned from this experience that it is crucial to have AVV competence to achieve a long-term survival in these challenging patients 2 as transplantation-free survival of those left with moderate or great AVV insufficiency was approximately 30% at 2 years after attempted AVV repair. 2 In sharp contrast, those who had common AVV replacement had 75% survival at 10 years.…”
Section: Outcomes Of Univentricular Repair In Patients With Common Atrioventricular Valvementioning
confidence: 99%